Executive summary for the Micronutrient Powders Consultation: Lessons Learned for Operational Guidance - Nyhus Dhillon, Christina; Sarkar, Danya; Klemm, Rolf D. W.; Neufeld, Lynnette M.; Rawat, Rahul; Tumilowicz, Alison; Namaste, Sorrel M. L. (John Wiley & Sons, 2017)
Iron deficiency anaemia is estimated to be the leading cause of years lived with disability among children. Young children's diets are often inadequate in iron and other micronutrients, and provision of essential vitamin and minerals has long been recommended. With the limited programmatic success of iron drop/syrup interventions, interest in micronutrient powders (MNP) has increased. MNP are a mixture of vitamins and minerals, enclosed in single-dose sachets, which are stirred into a child's portion of food immediately before consumption. MNP are an efficacious intervention for reducing iron deficiency anaemia and filling important nutrient gaps in children 6–23 months of age. As of 2014, 50 countries have implemented MNP programmes including 9 at a national level. This paper provides an overview of a 3-paper series, based on findings from the “Micronutrient Powders Consultation: Lessons Learned for Operational Guidance” held by the USAID-funded Strengthening Partnerships, Results, and Innovations in Nutrition Globally (SPRING) Project. The objectives of the Consultation were to identify and summarize the most recent MNP programme experiences and lessons learned for operationalizing MNP for young children and prioritize an implementation research agenda. The Consultation was composed of 3 working groups that used the following methods: deliberations among 49 MNP programme implementers and experts, a review of published and grey literature, questionnaires, and key informant interviews, described in this overview. The following articles summarize findings in 3 broad programme areas: planning, implementation, and continual programme improvement. The papers also outline priorities for implementation research to inform improved operationalization of MNP.